A Monolithically Integrated InGaN Nanowire/Si Tandem Photoanode Approaching the Ideal Bandgap Configuration of 1.75/1.13 eV. Issue 2 (22nd September 2016) - Fan, Shizhao; Shih, Ishiang; Mi, Zetian
Abstract : Indium gallium nitride (InGaN) nanowire arrays ( E g ≈1.75 eV) are monolithically integrated on a Si solar cell through a Si tunnel junction. With such a nearly ideal energy bandgap configuration, a saturated photocurrent density of 16.3 mA cm −2 is achieved under AM1.5G one sun illumination. The applied‐bias‐photon‐to‐current efficiency reaches 8.3% at 0.5 V versus normal hydrogen electrode.